Competence of nurses in health education in the Polish system of medical care - Pabiś, Małgorzata; Ślusarska, Barbara; Jarosz, Mirosław J.; Zarzycka, Danuta; Dobrowolska, Beata; Brzozowska, Agnieszka (Nursing in the 21st Century, 2011)
Introduction. Health care units are created to provide medical services, mainly those diagnostic and treatment, prophylactic, rehabilitation, nursing, as well as education. The statutory obligation to patients education is assigned to professions of physician, nurse and midwife. Objective. The objective of the study is to present the scope of the preparation of nurses for health education of patients in the Polish health care system. Material and methods. The study comprised 245 professionally active nurses. The research material was collected by means of especially designed questionnaire form, and the results obtained were subject to statistical analysis. Results. The majority of the nurses in the study reported the frequent undertaking of actions with respect to patients, those actions usually lasting for 15-20 minutes. The greatest number of nurses indicated themselves as being responsible for education. Conclusions. Nurses rated their preparation for carrying out education in very positive terms, and applied mainly conversation as the method of patient education. In the course of health education the respondents most often made use of the folders and brochures available.